The Legal Status of Certified Land Ownership of People Inhabiting around Limboto Lake - Sarson, Mohamad Taufiq Zulfikar (Universitas Negeri Semarang, 2020)
The raised ground (aanslibing) is land directly controlled by the State, and therefore every person who will control the land arise (aanslibing) must obtain prior permission from the government. The aim of this research was to determine and understand the process of issuance of ownership land certification around Limboto Lake after the silting up and determine the legal protection of owners certified land after the revitalization of the lake. The research was carried out at plains of Limboto Lake at two Kelurahan- Hutuo and Hunggaluwa, District of Gorontalo, Province of Gorontalo. Data collection employed interview and documentation techniques. The result of research showed that the issuance procces of certified land ownership around Limboto Lake was based on The Goverment Regulation No. 24 1997 concerning land registration. The regulation includes one of which was land with a hundred meters (100) distance from the lake border, land without certification at all, the land which is not under dispute, the land which is not under the bank fiduciary, the land which is under the authority of community proven by document legalizing the authority signed by the village head. For the ownership of land deposit, permit from the regional goverment is required. However, the National Land Body does no longer issue land ownership certification with reference to circulation letter of the Governor of Gorontalo Province. Legal protection for the holders of certified land after the revitalization activities may be attempted by the issuance of regional regulation draf that concerns the Provincial Space Management Planning of Strategic Areas of the Limboto Lake. However, legal protection for the certificates issued previously has not been available due to the onggoing procces of discussion of the Regional the Regulation Draft.